Emission of Methane From Enteric Fermentation: National Contribution and Factors Affecting it in Livestock - Budi Haryanto; A Thalib (Indonesian Center for Animal Research and Development, 2009)
Changing in atmosphere condition is affected by the quantity of gases produced from all activities on the earth. Gases that have effects on global warming are CO2, N2O, H2O, and CH4 (methane). Among other sources of methane are enteric fermentation of organic material from ruminants and feces decomposition. Methane production from ruminants is affected by several factors such as breed/type of animal, feed quality, environmental temperature and physiological status of the animal. Energy as methane in ruminants may reach 2 to 15% of the total energy consumption. To reduce the emission of methane from ruminants, it is necessary to apply a strategic feeding system for more efficient utilization of feed. Key words: Methane, global warming, ruminants, rumen fermentation